Upfront debulking surgery for high-grade serous ovarian carcinoma: current evidence - Tsonis, Orestis (Ann Transl Med, 2020)
High-grade serous ovarian carcinoma (HGSOC) is a leading cause of mortality among women worldwide. Currently, there is no clear consensus over the regime these patients should receive. The main two options are upfront debulking surgery with adjuvant chemotherapy or neoadjuvant chemotherapy followed by interval debulking surgery (IDS). The former approach is proposed to be accompanied by lower chemoresistance rates but could lead to severe surgical comorbidities and lower quality of life (QoL). Optimizing patient’s selection for upfront debulking surgery might offer higher progression-free and overall survival rates. Further studies need to be conducted in order to elucidate the predictive factors, which are favorable for patients undergoing upfront debulking surgery in cases of high-grade serous ovarian cancer.